Global research trends of hypertrophic cardiomyopathy from 2000 to 2022: Insights from bibliometric analysis - Zheng, Xifeng; He, Zhongkai; Li, Ming; Jia, Zhen (Frontiers in Cardiovascular Medicine, 2023)
Objectives To analyze the global research trends of hypertrophic cardiomyopathy (HCM) from 2000 to 2022 and explore new frontiers in this field. Methods We reviewed the literature in the Web of Science Core Collection database from January 2000 to August 2022 using the retrieval strategy of medical subject headings combined with text words. We focused on articles and reviews that were published in English. Relevant data of the target publications, such as title, authors, organizations, abstract, keywords, published date, journal, and number of citations, were collected. The R software with the “bibliometrix” and VOSviewer software was used to process and visualize the information. Results Among a total of 20,581 records related to HCM, 13,427 from 103 countries and regions, 8,676 affiliations, and 46,645 researchers were included. Most of the publications in this field were from the United States, followed by Japan, the United Kingdom, and China. We also report the top 10 institutions and most influential researchers, cited articles, and highest-frequency keywords (echocardiography, heart failure, sudden cardiac death, genetics, atrial fibrillation, magnetic resonance imaging/cardiac magnetic resonance, prognosis, mutation, arrhythmia, late gadolinium enhancement). In addition, keywords trend analysis indicated that the novel medicine Mavacamten, genetic diagnosis, and cardiac magnetic resonance have attracted the most attention for the treatment and diagnosis of HCM over the past five years. Conclusion The present study reports on the global research trends of HCM over the past two decades using bibliometric analysis. It may enlighten new frontiers in the diagnosis, treatment, and risk prevention of HCM.